2017
DOI: 10.1177/1932296817713025
|View full text |Cite
|
Sign up to set email alerts
|

Bolus Insulin Dose Error Distributions Based on Results From Two Clinical Trials Comparing Blood Glucose Monitoring Systems

Abstract: The ranges of insulin dose errors were statistically significantly smaller with EZ and CN than with all other BGMSs in this post hoc analysis. Differences in BGMS accuracy could result in clinically important differences in insulin dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, using only well performing devices for glucose measurement is of particular importance for clinical trials as confirmed in recently published studies. 16,17 Obviously, good device accuracy is a prerequisite to ensure patient safety. However, a suboptimal device performance may lead to other study-related problems such as potential bias in endpoints, potential inconsistencies between SMBG values and HbA1c, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…However, using only well performing devices for glucose measurement is of particular importance for clinical trials as confirmed in recently published studies. 16,17 Obviously, good device accuracy is a prerequisite to ensure patient safety. However, a suboptimal device performance may lead to other study-related problems such as potential bias in endpoints, potential inconsistencies between SMBG values and HbA1c, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate SMBG measurement results are crucial for adequate insulin dosing decisions by patients on insulin therapy. Modelling analyses showed that inaccurate BG measurements can lead to insulin dosing errors [ 1 , 3 , 4 , 39 , 40 ] which can adversely affect glycemic control and increase the risk of long-term complications in patients on intensive insulin therapy. In this study, negative median insulin dosing errors (too small insulin doses) were calculated for three systems (A, B, D) and positive median insulin dosing errors (too high insulin doses) were calculated for one system (C).…”
Section: Discussionmentioning
confidence: 99%